Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{9^{14}.25^5.8^7}{18^{12}.\left(25^2\right)^3.24^3}\)=\(\frac{9^{14}.25^5.8^7}{\left(9.2\right)^{12}.25^6.\left(8.3\right)^3}\)
=\(\frac{9^{14}.25^5.8^7}{9^{12}.2^{12}.25^6.8^3.3^3}\)=\(\frac{9^2.25^{-1}.8^4}{2^{12}.3^3}\)
=\(\frac{3^4.0,04.8^4}{8^4.3^3}\)=\(\frac{3.0,04}{1}\)
=3.0,04=0,12
k mình nhé
1/ 3(x - 2) = 9 => x - 2 = 3 => x = 5
2/ 3(x - 36) = 216 => x - 36 = 72 => x = 108
3/ (x - 3)3 = 33 => x - 3 = 3 => x = 6
4/ 2x = 32 => 2x = 25 => x = 5
5/ 3x - 16 = 2.74 : 73 = 14 => 3x = 30 => x = 10
6/ (6x - 39) : 3 = 201 => 6x - 39 = 603 => 6x = 642 => x = 107
7/ (3x - 15)2 = 81 => (3x - 15)2 = 92 => 3x - 15 = 9 => 3x = 24 => x = 8
8/ 3(x + 4) = 105 => x + 4 = 35 => x = 31
9/ 12x - 43 = 4.84 : 83 = 32 => 12x = 32 : 64 => 12x = 1/2 => x = 1/24
10/ 41 - (2x - 5) = 680 => 2x - 5 = -639 => 2x = -634 => x = - 317
2412 : 2412 + 2 . 22 - 94 : 93 + 50 .16
= 1 + 2^3 - 9 + 16
= 1 +8 -9 +16
= 16
\(24^{12}:24^{12}+2.2^2-9^4:9^3+5^0.16\)
\(=1+2^3-9+1.16\)
\(=1+8-9+16\)
\(=16\)
Ủng hộ nha